Effect of Aerobic Exercise on Improving Symptoms of Individuals With Schizophrenia: A Single Blinded Randomized Control Study - Wang, Peng-Wei; Lin, Huang-Chi; Su, Chwen-Yng; Chen, Ming-De; Lin, Kuo C.; Ko, Chih-Hung; Yen, Cheng-Fang (Frontiers in Psychiatry, 2018)
Introduction: Antipsychotic treatment can improve the symptoms of schizophrenia; however, residual symptoms after antipsychotic treatment are frequent. The effects of exercise on the symptoms of schizophrenic patients under antipsychotic treatment are inconclusive. The aim of this randomized case-control study was to examine the effects of aerobic exercise (AE) on the symptoms of schizophrenic patients receiving antipsychotic treatment. Methods: In total, 33 and 29 participants being treated with antipsychotics for schizophrenia were randomly assigned into the aerobic exercise (AE) group and the control group, respectively. The severities of schizophrenic symptoms were measured using the Chinese version of the Positive and Negative Syndrome Scale (PANSS) before, immediately after, and 3 months after the intervention in both groups. Results: In total, 24 participants (72.7%) in the AE group and 22 (75.9%) in the control group completed the study. The results indicated that the severities of positive symptoms and general psychopathology in the AE group significantly decreased during the 12 weeks of intervention but did not further significantly change during the 3-month follow-up period. The severities of negative symptoms in the AE group decreased significantly after 12 weeks of intervention and continued decreasing during the 3-month follow-up period. Interaction effects between time and group on the severities of symptoms on the negative and general psychopathology scales were observed. Conclusion: AE can improve the severities of symptoms on the negative and general psychopathology scales in individuals with schizophrenia being treated with antipsychotics.